The Role of Financial Literacy and Self-Control in Managing Students' Consumptive Behavior with PayLater Usage Decisions as a Mediating Variable - Adhitya Ananda, Nova; Utami Ady, Sri; Sayidah, Nur (Lafadz Jaya Publisher, 2024)
This study investigates the influence of Financial Literacy on Consumptive Behavior among students, with PayLater Usage as an intervening variable and Self-Control as a moderating variable. The rapid adoption of digital credit services, such as PayLater, has reshaped consumption patterns, particularly among young users, by promoting convenience and flexible payment options. This research aims to understand how financial literacy and self-control interact to influence students’ consumption behavior through PayLater usage. Using Structural Equation Modeling (SEM) with a sample of 100 students from the Faculty of Economics and Business at Universitas Teknologi Sumbawa, the study finds that Financial Literacy has a positive influence on both PayLater Usage and Consumptive Behavior. Interestingly, while financial literacy is generally expected to mitigate consumptive tendencies, it indirectly contributes to impulsive spending by encouraging the use of PayLater. PayLater Usage is identified as an intervening variable that strengthens the relationship between Financial Literacy and Consumptive Behavior, highlighting the role of convenience and perceived purchasing power in promoting consumption. Moreover, Self-Control negatively moderates the relationship between PayLater Usage and Consumptive Behavior, indicating that students with high self-control are less likely to exhibit impulsive spending despite using PayLater.